2020
DOI: 10.1002/jsfa.10410
|View full text |Cite
|
Sign up to set email alerts
|

Maternal dietary uridine supplementation reduces diarrhea incidence in piglets by regulating the intestinal mucosal barrier and cytokine profiles

Abstract: BACKGROUND Nucleotides play an important role in the regulation of cellular energy and protein homeostasis, which facilitate the repair, recovery and repletion of tissue function. This study tested the effects of maternal uridine (UR) supplementation during late pregnancy and lactation of sows on the immune function of the small intestine in neonatal and suckling piglets. RESULTS Results showed that compared to the control group, maternal dietary UR supplementation significantly decreased incidence of diarrhea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…As physiological factors, intestinal development, milk nutrients, stress factors, and feeding management could cause diarrhoea in piglets; thus, it is important to reduce diarrhoea in piglets by improving intestinal development. The results demonstrated dietary supplementation of uridine to sows could reduce the incidence of diarrhoea in suckling piglets ( Wu et al, 2020 ). A study on infants showed that nucleotide supplementation in infant formulas has anti-diarrhoeal effect and immune benefits ( Hess and Greenberg 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As physiological factors, intestinal development, milk nutrients, stress factors, and feeding management could cause diarrhoea in piglets; thus, it is important to reduce diarrhoea in piglets by improving intestinal development. The results demonstrated dietary supplementation of uridine to sows could reduce the incidence of diarrhoea in suckling piglets ( Wu et al, 2020 ). A study on infants showed that nucleotide supplementation in infant formulas has anti-diarrhoeal effect and immune benefits ( Hess and Greenberg 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on sows have suggested that the growth performance of piglets was improved by maternal yeast culture supplementation during gestation and lactation ( Kim et al., 2008 ; Hung 2015 ). Furthermore, maternal dietary uridine supplementation reduces diarrhoea incidence in piglets by regulating the intestinal mucosal barrier and cytokine profiles ( Wu et al, 2020 ). In addition, studies on broilers and weaned piglets have suggested that exogenous nucleotides could improve growth performance, intestinal enzyme activity and villus development ( Superchi et al., 2012 ; Daneshmand et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that oral administration of uridine stimulated intestinal development, promoted nucleotide transport, improved growth performance, and regulated the fatty acid composition and lipid metabolism in weaned piglets [41][42][43][44]. We have demonstrated that maternal dietary supplement UR contributed to reducing the occurrence of diarrhea by regulating cytokine secretion and intestinal mucosal barrier function of suckling pigs [45]. A recent study demonstrated that uridine was able to inhibit stemness of intestinal stem cells in 3D intestinal organoids and mice [46].…”
Section: Relationships Among Uridine and Glucose Lipid And Amino Acmentioning
confidence: 99%
“…During delivering, 5 ml blood was collected from eight sows per group from the jugular vein with a vacuum blood collection tube. In addition, on the day of birth, eight newborn male piglets (1•50 (SEM 0•204) kg) were randomly selected from each of the eight sows marked above as soon as they were born and they were kept apart from sows to avoid ingestion of colostrum (24) . And then, they were anaesthetised with an iv injection of sodium pentobarbital (50 mg/kg body weight) and bled by exsanguination (25) .…”
Section: Sample Collectionmentioning
confidence: 99%
“…Our previous research showed that UR had higher bioavailability than UMP in early weaned piglets (15) . Maternal dietary UR supplementation reduced diarrhoea incidence in piglets by regulating the intestinal mucosal barrier and cytokine profiles (24) , while this is the first research to study the effect of maternal dietary UR supplementation on reproductive performance in pigs. Previous studies reported that there is no effect on litter size and birth weight of piglets by supplementing yeast RNA with free nucleotides to sows 3 d before parturition (31) .…”
Section: Maternal Supplementation With Uridine Decreased Birth Mortalitymentioning
confidence: 99%